Ethnic hair: Thermoanalytical and spectroscopic differences. Issue 5 (11th March 2020) - Oliver, Marc A.; Coderch, Luisa; Carrer, Victor; Barba, Clara; Marti, Meritxell
Abstract: Background: The aim of this study is to characterize and detect the possible differences among the hair of three different ethnicities: African, Asiatic and Caucasian. Materials and Methods: The differences in water adsorption/desorption behaviour of hairs were studied using a thermogravimetric balance and compared with the analysis of the lipid distribution and order using synchrotron‐based Fourier transform infrared microspectroscopy. Besides, the thermal thermogravimetry (TG) and differential scanning calorimetry (DSC) analyses on human hair were executed. Results: Differences in the diffusion coefficients were evidenced. African hair exhibited increased permeability. Caucasian hair displayed a higher water absorption capability with increasing humidity but with a slow diffusion rate. The Asian fibre appeared to be more resistant to hydration changes. The spectroscopic analysis showed notable differences in the cuticle lipids. The African cuticle exhibited more lipids with a lower order bilayer. The outmost layer of Caucasian fibres contained more ordered lipids, and the Asian fibres show a very low level of lipids on the cuticle region. The DSC results indicate no difference in the thermal stability and TG showed higher water content in the Caucasian fibre and a possible lower cysteine disulphide bond content in the African hair matrix. Conclusion: The triple approach demonstrated the permeability differences among the ethnic fibres and their correlation with the properties of their cuticle lipids. These differences could have particular relevance to the hair care cosmetic market.